2014
DOI: 10.1016/j.jelekin.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Validity of trunk extensor and flexor torque measurements using isokinetic dynamometry

Abstract: This study aimed to evaluate the validity and test-retest reliability of trunk muscle strength testing performed with a latest-generation isokinetic dynamometer. Eccentric, isometric, and concentric peak torque of the trunk flexor and extensor muscles was measured in 15 healthy subjects. Muscle cross sectional area (CSA) and surface electromyographic (EMG) activity were respectively correlated to peak torque and submaximal isometric torque for erector spinae and rectus abdominis muscles. Reliability of peak to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 42 publications
2
41
0
2
Order By: Relevance
“…Maximal isometric strength in trunk flexion, extension, and lateral flexion was measured using the Humac NORM Isokinetic dynamometer (Humac NORM, Computer Sports Medicine, Stoughton, MA, USA) with the trunk extension‐flexion modular component. Isokinetic dynamometry has previously been reported to be a reliable and valid method for measuring trunk muscle strength . The measurement procedure of maximal isometric trunk strength has been described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximal isometric strength in trunk flexion, extension, and lateral flexion was measured using the Humac NORM Isokinetic dynamometer (Humac NORM, Computer Sports Medicine, Stoughton, MA, USA) with the trunk extension‐flexion modular component. Isokinetic dynamometry has previously been reported to be a reliable and valid method for measuring trunk muscle strength . The measurement procedure of maximal isometric trunk strength has been described previously …”
Section: Methodsmentioning
confidence: 99%
“…Isokinetic dynamometry has previously been reported to be a reliable and valid method for measuring trunk muscle strength. 28,29 The measurement procedure of maximal isometric trunk strength has been described previously. 14…”
Section: Trunk Muscle Strengthmentioning
confidence: 99%
“…There have been many studies on the extension and flexion strength of the trunk muscles, and the reported results have indicated that extension was stronger than flexion (Flint, 1958; Guilhem et al, 2014; Mayer et al, 1985; McNeill et al, 1980; Smidt et al, 1980). The reason for this is that the cross section during trunk extension is bigger than during flexion.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamometer used in our study was designed to enable trunk flexion and extension movements in an up-right position, with the feet positioned on two horizontal footplates, and the knees in a slightly flexed position (10°–20°). We measured trunk strength during trunk flexion from −10° to 50°, and during trunk extension from 50° to −10° (Davies and Gould, 1982; Guilhem et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…This technology allows the muscles to produce maximum muscle strength in all parts of the range of motion in concentric and eccentric contractions, which can not be obtained with tests with constant load. (13,14) Theoretically, the values obtained in isokinetic tests are more realistic in relation to muscle performance and helps to identify differences in the flexor and extensor muscles of the trunk and can these be crucial for analysis and stability control as seen for other joints. (15,9,16,4,17) Therefore, this study aimed to evaluate and compare the relationship flexors/extensors of the trunk muscles in sedentary men and women, asymptomatic through the isokinetic dynamometer.…”
Section: Introductionmentioning
confidence: 99%